Performance Analysis of FPGA based Diode Clamped Multilevel Inverter Fed Induction Motor Drive using Phase Opposition Disposition Multicarrier Based Modulation Strategy - Nunsavath Susheela; Satish Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Multilevel inverters (MLI) are becoming more popular over the years for medium and high power applications because of its significant merits over two level inverters. This paper presents an implementation of multicarrier based sinusoidal pulse width modulation technique for three phase seven level diode clamped multilevel inverter.  This topology is operated under phase opposition disposition pulse width modulation technique. The performance of three phase seven level diode clamped inverter is analyzed for induction motor (IM) load.  Simulation is performed using MATLAB/SIMULINK. Experimental results are presented to validate the effectiveness of the operation of the diode clamped multilevel inverter using field programmable gate array.